Study of Children’s Errors: A Window to the Process of Teaching and Learning of Mathematics - Goswami, Richa (Voices of Teachers and Teacher Educators, 2016)
Errors that children make are often seen only as flaws in learning and rarely as windows to their thought process. Two ways of looking at errors include; viewing them as learning stages and viewing them as gaps in learning. These views become even more pronounced in the teaching-learning process of a subject like Mathematics where the binary of correct answer and incorrect answer is seen to be clearly distinct. In this paper a study of children’s errors has been undertaken to understand what they indicate about the current knowledge of the learners. So, the new perspective being proposed in the paper is to view errors as an important resource for the teacher that would help them plan future teaching.